Alternative lengthening of telomeres: remodeling the telomere architecture - Conomos, Dimitri; Pickett, Hilda; Reddel, Roger (Frontiers in Oncology, 2013)
To escape from the normal limits on proliferative potential, cancer cells must employ a means to counteract the gradual telomere attrition that accompanies semi-conservative DNA replication. While the majority of human cancers do this by up-regulating telomerase enzyme activity, most of the remainder use a homologous recombination-mediated mechanism of telomere elongation known as alternative lengthening of telomeres (ALT). Many molecular details of the ALT pathway are unknown, and even less is known regarding the mechanisms by which this pathway is activated. Here, we review current findings about telomere structure in ALT cells, including DNA sequence, shelterin content, and heterochromatic state. We speculate that remodeling of the telomere architecture may contribute to the emergence and maintenance of the ALT phenotype.